The need for widely available genomic testing in rare eye diseases: an ERN-EYE position statement - Black, Graeme C; Sergouniotis, Panagiotis; Sodi, Andrea; Leroy, Bart P; Van Cauwenbergh, Caroline; Liskova, Petra; Grønskov, Karen; Klett, Artur; Kohl, Susanne; Taurina, Gita; Sukys, Marius; Haer-Wigman, Lonneke; et al. (Orphanet journal of rare diseases, 2021)
BACKGROUND: Rare Eye Diseases (RED) are the leading cause of visual impairment and blindness for children and young adults in Europe. This heterogeneous group of conditions includes over 900 disorders ranging from relatively prevalent disorders such as retinitis pigmentosa to very rare entities such as developmental eye anomalies. A significant number of patients with RED have an underlying genetic etiology. One of the aims of the European Reference Network for Rare Eye Diseases (ERN-EYE) is to facilitate improvement in diagnosis of RED in European member states. MAIN BODY: Technological advances have allowed genetic and genomic testing for RED. The outcome of genetic testing allows better understanding of the condition and allows reproductive and therapeutic options. The increase of the number of clinical trials for RED has provided urgency for genetic testing in RED. A survey of countries participating in ERN-EYE demonstrated that the majority are able to access some forms of genomic testing. However, there is significant variability, particularly regarding testing as part of clinical service. Some countries have a well-delineated rare disease pathway and have a national plan for rare diseases combined or not with a national plan for genomics in medicine. In other countries, there is a well-established organization of genetic centres that offer reimbursed genomic testing of RED and other rare diseases. Clinicians often rely upon research-funded laboratories or private companies. Notably, some member states rely on cross-border testing by way of an academic research project. Consequently, many clinicians are either unable to access testing or are confronted with long turnaround times. Overall, while the cost of sequencing has dropped, the cumulative cost of a genomic testing service for populations remains considerable. Importantly, the majority of countries reported healthcare budgets that limit testing. SHORT CONCLUSION: Despite technological advances, critical gaps in genomic testing remain in Europe, especially in smaller countries where no formal genomic testing pathways exist. Even within larger countries, the existing arrangements are insufficient to meet the demand and to ensure access. ERN-EYE promotes access to genetic testing in RED and emphasizes the clinical need and relevance of genetic testing in RED.
Keywords: Eye Diseases; Rare Diseases; Evropa; genetické testování; vzácné nemoci; Position statement; Genomics; oční nemoci; Humans; Genetic Testing; genomika; ERN-EYE; Genetic and genomic testing; Europe; dítě; lidé; Rare eye diseases; Child